Research on the integrated calculation method of current recovery and limited recovery in tight sandstone gas reservoirs - Dai, Jinyou; Wu, Junzhe; Shi, Yangyang; Lei, Xizhen; Pi, Sha (Frontiers in Earth Science, 2024)
Considering the differences in reserves and their utilization among gas reservoir area, utilization area and swept area, a reserves zoning producing model was established, and a method for integrating current recovery and limited recovery in gas reservoirs, the reserve analysis method, was proposed. The method was applied to calculate the current recovery and limited recovery of the gas reservoir and assess the potential of the gas reservoir to enhance the recovery, taking the Zizhou gas field in the Ordos Basin of China, the Shan2 tight sandstone gas reservoir, as an example. The results show that the method is able to simultaneously determine the current recovery, limited recovery, planar sweep efficiency, vertical sweep efficiency and gas driving efficiency of a gas reservoir by using four reserve parameters such as the gas reservoir area geological reserves, the producing area geological reserves, the swept area geological reserves, and the remaining geological reserves in the swept area when abandoned. This method is simple and easy to implement, and provides a new way for the evaluation of gas reservoir recovery potential and the study of improving the development method of gas reservoirs.